Performance of semi leafless variety of field pea under abiotic stress – A case study - Singh, R. K. (Indian Farming, 2026)
The productivity of pulse crops in the Bundelkhand region of Madhya Pradesh has been declining due to low adoption of improved varieties and recommended production technologies under limited irrigation conditions. The productivity of field pea at district, state, and national levels was reported as 9.81, 10.49, and 9.40 q/ha, respectively, against the varietal potential yield of 20–22 q/ha. To address this gap, Krishi Vigyan Kendra Chhatarpur introduced the drought-tolerant, semi-leafless dwarf field pea variety IPFD 12-2 under the National Food Security Mission during rabi 2022–23. Farmers were also trained on balanced fertiliser application along with the use of biofertilisers. Adoption of the improved production technology resulted in higher grain yield and net income compared to traditional farming practices.